Modelling Anglerfish Discard behaviour in Spanish North Atlantic Coast Fisheries - Santos-Blanco, Juan; Pérez-Contreras, María Nélida (2012)
Onboard sorting process for angler sh species in Spanish North Atlantic (ICES VIIIc, IXa) coastal sheries is reviewed. The length e ect analysis across the years sampled reveled an increasing trend in length of rst retention (L50) since 2000, the year when Minimum Landing Weight (MLW 500g) were implemented. Speci c di erences in the length-based sorting process were found, being the less valuable white angler discarded at larger lengths than the black species; further, the analysis found that discard decision is taken at narrower length range for black angler. This results indicate that shers recognize angler species even at low length sizes, conditioning the degree of adoption of MLW with regards to species relative market value.